Identification of YAC and cosmid clones encompassing the ZFX-POLA region using irradiation hybrid cell lines - Francis, Fiona; Benham, Frances; See, Chee Gee; Fox, Margaret; Ishikawa-Brush, Yumiko; Monaco, Anthony P.; Weiß, Birgit; Rappold, Gudrun; Hamvas, Renata M. J.; Lehrach, Hans (Genomics, 1994)
The human Xp21.3-p22.1 region is poorly mapped relative to other X chromosome regions. To target cosmid and YAC clones specifically from Xp21.3-p22.1 for rapid contig construction, a hybridization-based screening approach using irradiation hybrids has been used. Alu-PCR products generated from hybrid lines containing small overlapping fragments from Xp21-p22 were hybridized to an X chromosome cosmid library, and cosmids predicted by their hybridization pattern to map to the region of interest were analyzed by fluorescence in situ hybridization (FISH). Hybridization of the cosmids in pools to gridded YAC libraries identified 15 YACs, which were verified and tested for chimerism by FISH. Cosmid content analysis of the YACs defined two contigs, one with 12 YACs covering about 1.5 Mb and one with 3 YACs. Five YACs from the 12-YAC cluster had been previously recognized by DNA polymerase alpha (POLA). ZFX identified a single YAC; hence, the physical linkage of ZFX and POLA was demonstrated within the contig. Four YACs had been isolated previously with ZFX and these extend the contig to 2 Mb. Restriction mapping of several YACs demonstrates that ZFX and POLA are about 700 kb apart, a distance similar to that reported in the mouse between Zfx and Pola. The order of these two loci and two additional loci identified by homologous mouse linking clones was found to be conserved between human and mouse: tel-ZFX-DXCrc57-DXCrc140-POLA-cen. We have shown that YAC contigs can be rapidly constructed from targeted regions without the need for time-consuming YAC end rescue and chromosomal walking. This approach also generates a series of ordered cosmids, which is particularly valuable for marker generation in regions in which disease gene localization is hampered by low marker density.
Elektronische Reproduktion der Druck-Ausgabe
Online 25 May 2002
Gesehen am 31.03.2021